Media and Science and Technology-based Student Entrepreneurship Development Model at Pattimura University is a State University in Maluku Province - Teddy Christianto Leasiwal; Lussi R Loppies; Bin Raudha Arief Hanoeboen (Institute of Computer Science (IOCS), 2022)
The purpose of this activity is to create a document about the potential of the creative economy, and the chances of success in the Implementation of the Entrepreneurship Development Program for Young Creative Economy Actors for Beginners Based on Design, Media and Science and Technology. The research location is at Pattimura University, Ambon. This study took samples from 6 faculties at Pattimura University, namely FEB, FMIPA, FKIP, FPIK, Faculty of Engineering and FAPERTA. This study uses SWOT analysis which is used to obtain an overview of the strategic situation of an Economic Work Unit (UKE). is 0.55. Based on the SWOT map, it can be seen that the SWOT position is in quadrant 3, namely the Media and Science and Technology-based Student Entrepreneurship Development Model at Universities in Maluku facing enormous opportunities, but on the other hand facing several internal constraints/weaknesses. Pattimura University has received good attention. This is evidenced by the provision of entrepreneurship support facilities such as buildings, capital and training. However, it was also found that many student entrepreneurship did not go well. Due to lack of consistency in business, interest in business that is not in accordance with student skills, business culture is still low and the time period for being an entrepreneur at the University is short. In addition, students still find it difficult to divide their study time with the business they are engaged in.